Cutaneous Small-vessel Vasculitis after ChAdOx1 COVID-19 Vaccination: A Report of Five Cases. (June 2022) - Uh, Ji An; Lee, Soo Kyung; Kim, Joong Ho; Lee, Jae Ho; Kim, Myoung Shin; Lee, Un Ha
Amidst the Coronavirus Disease 2019 (COVID-19) pandemic, vaccination against severe acute respiratory syndrome 2 (SARS-CoV-2) is recommended for everyone over 18 years in South Korea, with the exception of pregnant women. Unexpected adverse cutaneous reactions after the COVID-19 vaccination have been recently reported. Cutaneous small-vessel vasculitis (CSVV) predominantly affects small blood vessels, defined as small intraparenchymal arteries, arterioles, capillaries, and venules, without any detectable involvement of non-cutaneous organs. We report five cases of CSVV after the ChAdOx1 COVID-19 vaccination in 44- to 68-year-old women. The symptoms commonly appeared within 2 days after vaccination. The lesion was localized to the lower limbs in four patients and spread to the upper limbs in one patient. All patients demonstrated a favorable response to oral methylprednisolone, antihistamines, and topical steroids. Considering the importance of the COVID-19 vaccination, clinicians should be aware of CSVV as a potential adverse event. Further studies are required to elucidate the causative link and pathogenesis.